Fenomenologi Hikikomori pada Tokoh Sagiri dalam Anime Eromanga Sensei Karya Ryouhei Takeshita - Sari, Anisya Yulinda; Syihabuddin, Syihabuddin (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2023)
This research is motivated by the Hikikomori phenomenology which occurs a lot in Japan among teenagers up to age 39. Hikikomori phenomenology is the act of a person when shutting himself at home or withdrawing from his social life for more than six months. In this article, the author examines the main t okoh of the anime Eromanga Sensei which experienced the hikikomori phenomenon, namely Izumi Sagiri. After the death of both her parents, Sagiri shut herself in the room and only communicated with her half-sister. The author uses research methodsthat are qualitative and descriptive analysis approaches. The author also analyzes using the phenomenological approach of Edmund Husseurl and the concept of Hikikomori in the character Sagiri. The results obtained from this study are that it is true that Sagiri experienced the Hikikomori phenomenon since his parents died, and has been locked up for a year. The cause of Hikikomori experienced by Sagiri is the child's sense of dependence on parents. So when she lost her parents, Sagiri experienced excessive anxiety.